SANKSI PERPAJAKAN MEMODERASI PENGARUH PENERAPAN SELF ASSESSMENT SYSTEM DAN WHISTLEBLOWING SYSTEM TERHADAP KEPATUHAN WPOP - Anggun Tyasmini, Ni Nyoman; Hasibuan, Henny Triyana (E-Jurnal Ekonomi dan Bisnis Universitas Udayana; VOLUME.13.NO.08.TAHUN.2024, 2024)
This research was conducted to obtain empirical evidence on the effect of the application of self-assessment system and whistleblowing system on WP compliance moderated by tax sanctions in Singaraja City. The research data was collected through questionnaires with the research respondents being WPOP registered at KPP Pratama Singaraja. The analysis techniques applied are multiple linear regression and Moderated Regression Analysis (MRA). Based on the results of the study, it shows that the implementation of the self assessment system and whistleblowing system has a negative and significant effect on WPOP compliance at KPP Pratama Singaraja. The acquisition of this research also proves that tax sanctions are able to moderate the impact of the application of the self-assessment system and whistleblowing system on WPOP compliance at KPP Pratama Singaraja. The theoretical implications of the acquisition of research that has been carried out provide evidence on the effect of WP compliance, especially regarding the self-assessment system, whistleblowing system and tax sanctions that can empirically prove the theories applied to this research, namely compliance theory and planned behavior theory.